Angiotensin Converting Enzyme (ACE) Inhibitory Activity of Peptide Fraction of Germinated Pigeon Pea (Cajanus cajan (L.) Millsp.) - Ketut Ratnayani; I Ketut Suter; Nyoman Semadi Antara; I Nengah Kencana Putra (Indonesian Journal of Chemistry, 2019)
During the germination process, seeds can release various types of peptides due to the degradation of storage proteins. Some of these peptides can have biological activity (bioactive peptides). The objective of this study was to determine the ACE inhibitory activity of germinated pigeon pea peptide extract at various germination times and to carry out the fractionation to the extract to get the most active peptide fraction. The results showed that the highest activity of peptide extract was found on the 4th-day germination of pigeon pea with an IC50 value of 63.46 μg/mL. The peptide extract was further fractionated by centrifugal ultrafiltration method and it was found that the peptide fraction < 3 kDa had the highest ACE inhibitory activity with an IC50 value of 57.79 μg/mL. The result of identification with the LCMS method to the fraction was able to detect 4 types of the peptide with a molecular weight of 230.304, 294.303, 441.436, and 570.591 Da. These results suggested that the peptide fraction of germinated pigeon pea has the potency as an ACE inhibitory nutraceutical.